Detecting Everyday Action Deficits in Alzheimer's Disease Using a Nonimmersive Virtual Reality Kitchen. (10th March 2014) - Allain, Philippe; Foloppe, Déborah Alexandra; Besnard, Jérémy; Yamaguchi, Takehiko; Etcharry-Bouyx, Frédérique; Le Gall, Didier; Nolin, Pierre; Richard, Paul
Abstract Alzheimer's disease (AD) causes impairments affecting instrumental activities of daily living (IADL). Transdisciplinary research in neuropsychology and virtual reality has fostered the development of ecologically valid virtual tools for the assessment of IADL, using simulations of real life activities. Few studies have examined the benefits of this approach in AD patients. Our aim was to examine the utility of a non-immersive virtual coffee task (NI-VCT) for assessment of IADL in these patients. We focus on the assessment results obtained from a group of 24 AD patients on a task designed to assess their ability to prepare a virtual cup of coffee, using a virtual coffee machine. We compared performance on the virtual task to an identical daily living task involving the actual preparation of a cup of coffee, as well as to global cognitive, executive, and caregiver-reported IADL functioning. Relative to 32 comparable, healthy elderly (HE) controls, AD patients performed worse than HE controls on all tasks. Correlation analyses revealed that NI-VCT measures were related to all other neuropsychological measures. Moreover, regression analyses demonstrated that performance on the NI-VCT predicted actual task performance and caregiver-reported IADL functioning. Our results provide initial support for the utility of our virtual kitchen for assessment of IADL in AD patients. (JINS, 2014, 20, 1–10)